Characterization and assessment of the wideband magnetic properties of nanocrystalline alloys and soft ferrites. Issue 15 (13th August 2018) - Ferrara, Enzo; Fiorillo, Fausto; Beatrice, Cinzia; Dobák, Samuel; Ragusa, Carlo; Magni, Alessandro; Appino, Carlo
Abstract: Abstract : Efficient applications of magnetic cores in sensing and power electronics require low-loss and versatile soft magnetic materials, with excellent response on a wide range of frequencies. This objective is traditionally pursued with ferrite and Permalloy tape cores, available under a variety of properties. Comparable and even superior soft magnetic behavior can, however, be obtained with amorphous and nanocrystalline alloys, with the latter, in particular, combining flexible response to thermal treatments with high magnetic saturation. Broadband precise magnetic characterization of these materials, crucial to their use as inductive cores, is fully appreciated when associated with assessment by physical modeling. Comprehensive measuring approach and significant results obtained in sintered soft ferrites and nanocrystalline ribbons up to 1 GHz are highlighted in this paper. We show how broadband loss and permeability behaviors can be quantitatively interpreted in the framework of the loss separation concept, applied to eddy current and spin damping dissipation mechanisms.